2021
DOI: 10.1002/ijc.33857
|View full text |Cite
|
Sign up to set email alerts
|

Can miRNAs be useful biomarkers in improving prognostic stratification in endometrial cancer patients? An update review

Abstract: Endometrial cancer (EC) is the most common gynecological cancer, with annual incidence rates in Western countries ranging between 15 and 25 per 100 000 women. About 15% to 20% of patients with EC have high‐risk disease and follow an aggressive clinical course. Unfortunately, the assessment of histologic parameters is poorly reproducible and conventional clinicopathological and molecular features do not reliably predict either the patient's response to the available treatments or the definition of personalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The integration of molecular data with histopathological features in EC is becoming more and more important since TCGA proposed to stratify EC in different groups, according to their molecular alterations (POLE-ultramutated; copy-number low/NSMP and hypermutated/MMRd groups; copy-number high/p53 mutant group) [31]. Several studies have investigated the importance of biomarkers in distinguishing different EC subclasses with different outcomes [3][4][5][6][7][8]. Among molecular markers relevant in EC, ARID1A alterations seem to play an important role in defining the clinical and prognostic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of molecular data with histopathological features in EC is becoming more and more important since TCGA proposed to stratify EC in different groups, according to their molecular alterations (POLE-ultramutated; copy-number low/NSMP and hypermutated/MMRd groups; copy-number high/p53 mutant group) [31]. Several studies have investigated the importance of biomarkers in distinguishing different EC subclasses with different outcomes [3][4][5][6][7][8]. Among molecular markers relevant in EC, ARID1A alterations seem to play an important role in defining the clinical and prognostic features.…”
Section: Discussionmentioning
confidence: 99%
“…The same criteria are also used to tailor surgery and to select patients for adjuvant therapy. Molecular alterations have been integrated into the characterization of ECs since the Cancer Genome Atlas (TCGA) project identified four distinct groups based on molecular alterations [3][4][5][6][7][8][9][10][11]. The SWI/SNF (switch/sucrose nonfermenting chromatin remodeling) complex is the pattern of proteins more investigated in EC.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbingly, the average age of the patients gradually decreased. EC is the third most commonly diagnosed cancer among females aged 20–39 years in the United States, with an annual occurrence rate of approximately 15–25 per 100,000 individuals [ 2 ]. Approximately 65,950 EC cases and 12,550 deaths were reported in 2021 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the global incidence and mortality of endometrial cancer (EC), regions, such as North America and Europe, rank at the front of global [1]. In the United States, endometrial cancer has been identified as the third most common cancer in women aged between 20 and 39, with annual incidence rates of about 15 to 25 per 100,000 women [2]. Approximately, 65,950 new cases of EC and 12,550 related deaths have been reported in 2021 [3].…”
Section: Introductionmentioning
confidence: 99%